Penerapan Hazard Identification, Risk Assesment And Determining Control (HIRADC) Dalam Upaya Mengurangi Kecelakaan Kerja Di PT Wijaya Karya Beton Tbk PPB Majalengka - Muhanafi, Muhammad Yulfa, Tarwaka, PGDip Sc, M.Erg, Sri Darnoto S.KM M.PH (2015)
PT. Wijaya Karya Majalengka is one of the precast concrete industry, the product of electrical poles and concrete piles centrifuges is the biggest product in Indonesia. Production activities at risk of workplace accidents. Workplace accidents can be prevented by application of the Hazard Identification, Risk Asesment, and Determining Control (HIRADC). HIRADC aims to identify potential hazards in the workplace is the link between the workers, tasks, equipment and work environment. This study aims to determine the application HIRADC in an effort to reduce the risk of accidents at work in PT Wijaya Karya Beton Majalengka. Type of research is analytic descriptive research with a total sample of 31 samples were obtained using Proportionate Stratified random sampling formula. The result showed the potential danger of high levels contained in the spinning process, stressing, and foundries, while the high risk contained in the welding and grinding process. Potential danger may come from the tool or machine work, workplace environment, and even the behavior of workers less secure.